Beyond refuges: Identifying temporally dynamic havens to support ecological resistance and resilience to climatic disturbances. (May 2019) - Selwood, Katherine E.; Cunningham, Shaun C.; Mac Nally, Ralph
Abstract: Little can be done by natural resource managers to abate climatic extremes such as drought, so assisting ecological communities to withstand and to recover from extreme events is likely to be an effective strategy for reducing the impacts of changing climate conditions on biodiversity. We present a framework for identifying locations that are likely to increase the capacity of biota to withstand disturbances ('resistance') and to recover when adverse conditions abate ('resilience'). Our study ecosystem was the river red-gum ( Eucalyptus camaldulensis ) floodplain forests of the Murray River, southeastern Australia. We tracked forest-stand condition of river red-gum forests during and after a prolonged drought (the Big Dry) using models based on remotely sensed data and ground-truthed vegetation measurements of forest-stand condition. Native birds and small mammals respond positively to stand condition. We used spatial optimization to rank the region based on forest-stand condition at multiple time-points during a 13 yr drought and 2 yr after the drought ceased. We identified areas that ranked in the top portion of the landscape in either period to identify 'resistance havens' and 'resilience havens' respectively and assessed the extent to which these overlapped. Although there was overlap in the top ranked areas, there were differences in the areas identified as havens (top 25% ranking) in both periods, with a 55.5% overlap between areas identified as havens in either period. This overlap was lower (40.1%) when considering the most highly ranked (top 10%) areas. Concentrating only on locations that provide protection from adverse conditions (i.e. refugia) is likely to be ineffective for conservation management in increasingly changeable environmental conditions because areas that facilitate resistance will not necessarily be the same as areas that support recovery. Acknowledging and incorporating the concepts of ecological resistance and resilience into landscape management is vital if managers are to lessen the ecological effects of intensified disturbance regimes associated with climate change.